KETERAMPILAN KOMUNIKASI HIPNOTIC KONSELING - HIMSONADI HIMSONADI (Al-Tazkiah : Jurnal Bimbingan dan Konseling Islam, 2019)
Counselling communication skills are one of the competencies that must be possessed by a counselling teacher, both verbal and non-verbal communication. The success of counselling is largely determined by the ability of counsellors to master effective counselling communication skills and evidence of mastery of counselling communication skills is manifested in the form of effective communication practices with techniques in the counselling process. In addition to mastering counselling techniques in general, counsellors must have the ability to influence, because the success of counselling can not be separated from the extent to which the counsellor influences the counselee being served. With the ability to influence the counsellor, BK can easily help the counselee. Techniques used by counsellors to influence counselees as offered in this journal, including counsellors must master the principles of hypnosis counselling and can use hypnosis counselling language patterns, both of which can be applied at each individual counselling stage.